2006
DOI: 10.1111/j.1365-2052.2006.01482.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of melanocortin 4 receptor (MC4R) and high mobility group AT‐hook 1 (HMGA1) polymorphisms with pig growth and fat deposition traits

Abstract: The aim of this study was to analyse the combined effect of melanocortin 4 receptor (MC4R) and high mobility group AT-hook 1 (HMGA1) polymorphisms on growth and fatness traits in Duroc pigs. No significant interaction was observed between MC4R and HMGA1 for back-fat traits. An additive mode of inheritance of both gene effects was found for average daily gain and lean meat content. Maximum mean differences from combined genotypic effects were over 2 mm for back fat, 70 g/day for average daily gain and 2% for le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 9 publications
2
27
0
3
Order By: Relevance
“…In particular, HMGA1 polymorphism was previously found to be associated with fat deposition in European commercial lines (24,25). Another gene of importance for the adipogenic process in the SSC7 QTL interval might be the cyclin-dependent kinase inhibitor (CDKN1A) known to regulate adipocyte number in mammals (36).…”
Section: Physiological Effects Of Genotype At Ssc7 Qtlmentioning
confidence: 99%
“…In particular, HMGA1 polymorphism was previously found to be associated with fat deposition in European commercial lines (24,25). Another gene of importance for the adipogenic process in the SSC7 QTL interval might be the cyclin-dependent kinase inhibitor (CDKN1A) known to regulate adipocyte number in mammals (36).…”
Section: Physiological Effects Of Genotype At Ssc7 Qtlmentioning
confidence: 99%
“…Here we would like to focus our attention on several SNPs which seem to be the most interesting. For instance, the effect of MC4R polymorphism on growth rate (average daily gains) did not reach the significance criteria, although based on results obtained by Stachowiak et al (2005), Jakubka et al (2006), Kim et al (2006) and Meidtner et al (2006) its effect on the trait was indicated. On the other hand, results reporting a significant effect of DECR1 polymorphism on GR, presented in this paper, are concordant with the extended analysis published recently by our team (Kaminski et al 2009), but different from those described by Amills et al (2005).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, these markers may be associated with a larger effect on the variation of the corresponding trait and because they do not rely necessarily on LD, they are expected to be reproducible across diverse populations offering more accurate and reproducible predictions of the levels of the trait even in untested populations [73]. For example, a functional variant observed in the MC4R gene has been shown to have consistent effects on pig growth and fat deposition traits across populations and environments [42][43][44]78].…”
Section: Introductionmentioning
confidence: 99%